2003
DOI: 10.1046/j.1537-2995.2003.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of national HIV, HCV, and HTLV antibody testing algorithms based on sequential screening immunoassays

Abstract: The results presented in this report demonstrate that the sequential use of screening immunoassays before immunoblot testing can significantly reduce both the number of immunoblot tests and proportion of indeterminate results, without impacting sensitivity, thereby improving algorithm efficiency and simplifying donor management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 23 publications
2
43
0
Order By: Relevance
“…One could test simultaneously with two assays and exclude donors reactive with both since these subjects have the highest probability to be positive with NAT and/or Immunoblot (Choudhury et al, 2011). Nevertheless, two tests increase the cost of the screening unless a sequential screening strategy is used (Seed et al, 2003). Another solution would be to use the strength of antibody reactivity as predictive marker of true-positive results and viremia in asymptomatic HCV infected people (Acar et al, 2010; Contreras et al, 2010; Kiely et al, 2010; Stramer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One could test simultaneously with two assays and exclude donors reactive with both since these subjects have the highest probability to be positive with NAT and/or Immunoblot (Choudhury et al, 2011). Nevertheless, two tests increase the cost of the screening unless a sequential screening strategy is used (Seed et al, 2003). Another solution would be to use the strength of antibody reactivity as predictive marker of true-positive results and viremia in asymptomatic HCV infected people (Acar et al, 2010; Contreras et al, 2010; Kiely et al, 2010; Stramer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This algorithm has shown an elevated rate of inconclusive results and a high cost. The use of two EIA from different manufacturers for HTLV screening before confirmatory testing has been suggested in order to decrease false-reactive results [Rouet et al, 2001;Thorstensson et al, 2002;Seed et al, 2003;Jacob et al, 2007]. PCR is considered a gold standard for diagnosis of HTLV-1/2 because of its high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The dual EIA algorithm we employed, which involves testing each sample that was repeat-reactive with the primary screening EIA using a different EIA, as previously suggested by Seed et al, 27 was shown to have high positive and negative predictive values, and could thus be utilized in blood services that usually do not perform confirmatory tests for HTLV due to the high cost of commercial WBs and unavailability of commercial HTLV PCR tests. This is the case for the majority of blood services in Brazil, where screening for HTLV is obligatory, but not the confirmation.…”
Section: Carneiro-proietti Et Almentioning
confidence: 99%